Strategi Pembelajaran dan Pendekatan Matematika - Handayani, Rona; Rarasafitri, Tania; Rahmayani, Rahmayani; Fadillah, Juni; Lubis, Reza Handika Winata (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
Mathematics learning aims not only to enhance numeracy skills but also to develop logical and analytical thinking abilities essential for problem-solving in various fields, including science, technology, and economics. However, its abstract nature often makes it challenging for students to comprehend. Therefore, effective learning strategies and approaches are crucial to achieving educational objectives. This study explores diverse mathematics learning strategies to improve learning effectiveness, focusing on organizing, delivering, and managing instruction. Additionally, it examines both teacher- and student-centered approaches, as well as contextual and thematic methods that foster a more engaging and meaningful learning environment. This research employs a qualitative method with a literature review approach, gathering and analyzing data from various relevant sources. The findings suggest that selecting appropriate learning strategies and approaches can enhance student engagement and learning outcomes, ultimately fostering creative, critical, and analytical thinking skills crucial for real-life applications.